Ulga prorodzinna w kontekście formy opodatkowania - Martynowicz, Aleksandra (Family Tax Allowance in the Context of Taxation Form, 2008)
Family tax allowance was introduced in 2007. It gives the possibility of reducing tax, depending on the number of children in a family. The paper describes the construction and the terms of using the allowance. It presents the level of income which allows to make full deduction. It shows who can gain from this preference and which tax payers are excluded from the group of beneficiaries. It also points out the threats connected with using the allowance.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 32, s. 68-71